Respuesta :

Answer: f(7) = -128

g(7) =  26

Equation of f(x):  f(x)= -11x-51

Equation of g(x): g(x)=3x+5

Step-by-step explanation:

Rate of change of a function: [tex]\dfrac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]

From the table. Rate of change in f(x)= [tex]\dfrac{f(1)-f(0)}{1-0}=\dfrac{-62+51}{1}=-11[/tex]

Rate of change in g(x)= [tex]\dfrac{g(1)-g(0)}{1-0}=\dfrac{8-5}{1}=3[/tex]

Also, the rate of change throughout the function is the same, hence both are linear functions.

Equation of linear function:  [tex]f(x)=mx+c[/tex], where m= rate of change of function, c = f(x) at x=0.

From table, f(0)= -51 , g(0)=5

Equation of f(x): f(x)= -11x-51

Equation of g(x): g(x)=3x+5

f(7) = -11(7)-51 = -77-51 = -128

g(7) = 3(7)+5 = 21+5 = 26

f(7) = -128

g(7) =  26